Brain imaging measurements of fibrillar amyloid‐β burden, paired helical filament tau burden, and atrophy in cognitively unimpaired persons with two, one, and no copies of the APOE ε4 allele. Issue 4 (16th January 2020) - Ghisays, Valentina; Goradia, Dhruman D.; Protas, Hillary; Bauer, Robert J.; Devadas, Vivek; Tariot, Pierre N.; Lowe, Val J.; Knopman, David S.; Petersen, Ronald C.; Jack, Clifford R.; Caselli, Richard J.; Su, Yi; et al.
Abstract: Introduction: We previously characterized associations between brain imaging measurements of amyloid‐β (Aβ) plaque burden and apolipoprotein E (APOE ) ε4 gene dose in a small number of cognitively unimpaired late‐middle‐aged APOE ε4 homozygotes (HMs), heterozygotes (HTs), and noncarriers (NCs). We now characterize cross‐sectional Aβ plaque, tau tangle, and cortical atrophy (neurodegeneration) measurements, classifications, and associations with age in a larger number of unimpaired HMs, HTs, and NCs over a wider age range. Methods: We analyzed 11 C Pittsburgh compound B (Aβ) positron emission tomography (PET), flortaucipir (tau) PET, and volumetric magnetic resonance imaging data from 164 study participants of age 47–86 years, including 26 APOE ε4 HMs, 48 HTs, and 90 NCs matched for age and sex. Results: Aβ PET measurements rose, plateaued at the respective ages of 68 and 76, and then declined with age in unimpaired HM and HT groups. Compared with NCs, these two groups began to have significantly higher Aβ PET measurements at ages 62 and 70, respectively, and no longer had significantly higher measurements by ages 71 and 78, respectively. They began to have significantly higher entorhinal cortex tau PET measurements at ages 66 and 70, respectively, and no longer had significantly higher measurements by ages 74 and 78, respectively. Brain atrophy measurements tended to decline slowly with age in all three genetic groups. Their elevated tau PET measurements were attributable to those with positive Aβ PET scans. 41.0%, 18.0%, and 5.0% of the 47‐ to 70‐year‐old HMs, HTs, and NCs and 25.0%, 79.0%, and 38.0% of the 71‐ to 86‐year‐old HMs, HTs, and NCs had positive Aβ PET scans, and the long‐term recall memory scores are significantly higher in the older HMs than in HT and NC groups, suggesting resistance to Aβ deposition in those HMs who remained unimpaired at older ages. Conclusions: This study provides information about Aβ plaque burden, tau tangle burden, and neurodegeneration in cognitively unimpaired persons at three levels of genetic risk for AD. Unimpaired APOE ε4 HMs can be studied before their 70s to evaluate the understanding of factors, processes, and interventions involved in the predisposition to and prevention of AD, and after their 70s, to discover factors, processes, and interventions involved in the resilience or resistance to and prevention of AD.